2008
DOI: 10.1073/pnas.0801971105
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of tRNA nucleotidyltransferases: A small deletion generated CC-adding enzymes

Abstract: CCA-adding enzymes are specialized polymerases that add a specific sequence (C-C-A) to tRNA 3 ends without requiring a nucleic acid template. In some organisms, CCA synthesis is accomplished by the collaboration of evolutionary closely related enzymes with partial activities (CC and A addition). These enzymes carry all known motifs of the catalytic core found in CCA-adding enzymes. Therefore, it is a mystery why these polymerases are restricted in their activity and do not synthesize a complete CCA terminus. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(140 citation statements)
references
References 26 publications
6
133
0
1
Order By: Relevance
“…To rule out that the reduced A-addition represents an effect specific to the tRNA Tyr substrate, the determination of MichaelisMenten kinetic parameters was conducted with another substrate, yeast tRNA Phe , one of the most commonly used substrates in CCA adding reactions. 16,17,21 To analyze the efficiency of the terminal A-addition. While the observed K M values of 0.09 mM and 0.11 mM did not differ significantly between the wt enzyme and the D139A variant (p D 0.8), the latter variant showed a strongly reduced k cat value of 0.008 s ¡1 , compared to 0.119 s…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To rule out that the reduced A-addition represents an effect specific to the tRNA Tyr substrate, the determination of MichaelisMenten kinetic parameters was conducted with another substrate, yeast tRNA Phe , one of the most commonly used substrates in CCA adding reactions. 16,17,21 To analyze the efficiency of the terminal A-addition. While the observed K M values of 0.09 mM and 0.11 mM did not differ significantly between the wt enzyme and the D139A variant (p D 0.8), the latter variant showed a strongly reduced k cat value of 0.008 s ¡1 , compared to 0.119 s…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Figure 2. Biochemical analysis of conserved amino acids in motif C of the human CCA-adding enzyme.…”
Section: ¡1mentioning
confidence: 99%
See 1 more Smart Citation
“…In organelles, the tRNA nucleotidyltransferase only has to add two nucleotides, C and A, to the 39 end because a high number of plastid tRNA genes encode a C at the 39 end (Mayer et al, 2000;Tomita et al, 1996). Aquifex aeolicus, Deinococcus radiodurans, some cyanobacteria and recently Bacillus halodurans, Bacillus clausii and Geobacter sulfurreducens have been found to contain separate enzymes for the addition of A and C residues to tRNA in vivo (Bralley et al, 2005(Bralley et al, , 2009Neuenfeldt et al, 2008;Seth et al, 2002;Tomita & Weiner, 2001. In Streptomyces coelicolor less than a third of the tRNA genes encode the CCA end and the product of SCO3896, the S. coelicolor CCase, is essential in this process (Bralley et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In some organisms a single CCase modifies the 39 end of damaged or immature tRNAs in a template-independent manner. Interestingly, it has been shown that in Aquifex aeolicus (Tomita & Weiner, 2001), Synechocystis sp., Deinococcus radiodurans (Tomita & Weiner, 2001), Bacillus halodurans (Bralley et al, 2005), Bacillus clausii (Neuenfeldt et al, 2008) and Geobacter sulfurreducens (Bralley et al, 2009) there are two enzymes, one of which adds the CC dinucleotide and one that adds the terminal A. In B. subtilis there is only a single gene coding for CCase (Raynal et al, 1998).…”
Section: Introductionmentioning
confidence: 99%